National trend of utilization, clinical and economic outcomes of transcatheter aortic valve replacement among patients with chronic obstructive pulmonary disease. (3rd August 2019) - Ji Kwak, Min; Bhise, Viraj; Warner, Mark T.; Balan, Prakash; Nguyen, Tom C.; Estrera, Anthony L.; Smalling, Richard W.; Dhoble, Abhijeet
Abstract: Objectives: We aimed to trend the utilization of transcatheter aortic valve replacement (TAVR) among COPD patients, compare its outcomes to surgical aortic valve replacement (SAVR) and assess any social disparities in its outcomes. Background: Patients with chronic obstructive pulmonary disease (COPD) have been increasingly undergoing TAVR, but studies to evaluate the national trend of TAVR utilization and outcomes are still lacking. Methods: We conducted a retrospective observational study using a nationally representative database, the National Inpatient Sample (NIS). Results: From 2010 to 2014, the proportion of TAVR among COPD patients has increased from <1% to >50%. Patients who underwent TAVR were older, more likely to be women or white, carried more public insurance and had more comorbidities. There was no overall difference in mortality between TAVR and SAVR (2.74% vs. 2.59%, p = .860), and it has been consistently similar over time. However, patients with TAVR had shorter length of stay in the hospital after the procedure and were more likely to be discharged home than the SAVR group. Among the TAVR group, there were no gender, race or insurance disparities for in-hospital mortality, but female gender was related to lower discharge home rate, higher cost and longer stay in hospital. Conclusions: The rate of TAVR among COPD patients has been increasing nationally since 2011. In spite of higher comorbidities, TAVR did not show a difference in hospital mortality compared to SAVR but demonstrated shorter length of stay and more home discharges. This suggests that TAVR is a viable and potentially better option for patients with COPD.